Stereotypic behaviours in frontotemporal dementia and progressive supranuclear palsy. (December 2018) - Prioni, Sara; Redaelli, Veronica; Soliveri, Paola; Fetoni, Vincenza; Barocco, Federica; Caffarra, Paolo; Scaglioni, Augusto; Tramacere, Irene; Girotti, Floriano
Abstract: Introduction: The behavioural variant of frontotemporal dementia (bvFTD), and the Richardson variant of progressive supranuclear palsy (PSP-RS) share several clinical signs and symptoms. Since stereotypic behaviours are fairly common in bvFTD, and are also described in other degenerative dementias including Alzheimer's disease, and parkinsonisms with dementia, we aimed to examine the extent to which stereotypies also characterise PSP-RS. Methods: We compared 53 bvFTD patients with 40 demented PSP-RS patients, seen consecutively as outpatients at four Italian Hospitals. Patients were assessed by the Neuropsychiatric Inventory (NPI); Mini-Mental State Examination (MMSE) and Frontal Assessment Battery (FAB) for cognitive functions; Stereotypy Rating Inventory (SRI) for stereotypies; Unified Parkinson's Disease Rating Scale (UPDRS) for motor function; and Activities of Daily Living (ADL) to assess autonomy in daily life. Results: The groups did not differ for age, illness duration, cognitive functions or total NPI score; PSP-RS had significantly more depressive symptoms and greater motor and autonomy compromise than bvFTD. The groups did not differ significantly on total SRI score, but bvFTD had significantly more cooking and eating stereotypies. Twenty-three (57.5%) PSP-RS and 43 (81%) bvFTD patients had at least one stereotypy; 16/23 (69.5%) PSP-RS and 9/43 (20.9%) bvFTD patients appeared aware of their stereotypies. Conclusion: Stereotypies were common in our demented PSP-RS patients. Further studies on earlier stage non-demented PSP patients are required to ascertain whether stereotypies are characteristic of PSP in general or are confined to PSP-RS, and whether they may be used to suggest a PSP diagnosis early in disease course.